Decoration of voids with rhenium and osmium transmutation products in neutron irradiated single crystal tungsten. (December 2019) - Lloyd, Matthew J.; Abernethy, Robert G.; Gilbert, Mark R.; Griffiths, Ian; Bagot, Paul A.J.; Nguyen-Manh, Duc; Moody, Michael P.; Armstrong, David E.J.
Abstract: High temperature, neutron irradiated single crystal tungsten, with a post irradiation composition of W - 1.20 ± 0.11 at.%Re - 0.11 ± 0.05 at.%Os - 0.03 ± 0.01 at.%Ta was characterised using a combination of Atom Probe Tomography (APT) and Scanning Transmission Electron Microscopy (STEM). APT showed that within nanoscale clusters of Re/Os, the atomic density was above the theoretical limit. Complimentary High Angle Annular Dark Field (HAADF) imaging shows that some clusters contain voids at their centre which are leading to APT aberrations and enhancing the atomic density. High resolution Energy Dispersive X-ray (EDX) spectroscopy shows that voids are decorated with a shell of rhenium with a small osmium cluster to one side. Graphical abstract: Unlabelled Image